2010
DOI: 10.1186/1471-2407-10-635
|View full text |Cite
|
Sign up to set email alerts
|

A panel of kallikrein markers can predict outcome of prostate biopsy following clinical work-up: an independent validation study from the European Randomized Study of Prostate Cancer screening, France

Abstract: BackgroundWe have previously shown that a panel of kallikrein markers - total prostate-specific antigen (PSA), free PSA, intact PSA and human kallikrein-related peptidase 2 (hK2) - can predict the outcome of prostate biopsy in men with elevated PSA. Here we investigate the properties of our panel in men subject to clinical work-up before biopsy.MethodsWe applied a previously published predictive model based on the kallikrein panel to 262 men undergoing prostate biopsy following an elevated PSA (≥ 3 ng/ml) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 19 publications
3
39
0
3
Order By: Relevance
“…The OPKO panel has been demonstrated in over 8,500 patients to predict the probability of cancer-positive biopsies in men suspected of having PCa. Retrospective studies have shown that the use of the panel could eliminate over 50% of unnecessary biopsies, with a probability of delaying diagnosis of a high grade cancer of only 0.6% (and this small population of men would be followed with active surveillance) [6,9].…”
Section: Kscore Prostate Cancer Test (Opko Health)mentioning
confidence: 99%
See 1 more Smart Citation
“…The OPKO panel has been demonstrated in over 8,500 patients to predict the probability of cancer-positive biopsies in men suspected of having PCa. Retrospective studies have shown that the use of the panel could eliminate over 50% of unnecessary biopsies, with a probability of delaying diagnosis of a high grade cancer of only 0.6% (and this small population of men would be followed with active surveillance) [6,9].…”
Section: Kscore Prostate Cancer Test (Opko Health)mentioning
confidence: 99%
“…This panel is based on markers used in a series of studies conducted in Europe and the U.S, assessing risk for clinically significant PCa [4][5][6][7][8][9][10]. The OPKO panel has been demonstrated in over 8,500 patients to predict the probability of cancer-positive biopsies in men suspected of having PCa.…”
Section: Kscore Prostate Cancer Test (Opko Health)mentioning
confidence: 99%
“…A panel of four serum kallikreins (total PSA, free PSA, intact PSA, and human kallikrein protein 2 (hK2) has received extensive evaluation in the pre-biopsy setting and is commercially marketed as the 4Kscore Test (4K, OPKO Lab, Nashville, TN) [19][20][21][22][23]24•]. The algorithm representing these components was initially derived from data based on participants within the European Randomized Study of Prostate Cancer Screening (ERSPC) and Prostate Testing for Cancer and Treatment (ProtecT) studies.…”
Section: Emerging Serum Biomarkersmentioning
confidence: 99%
“…In addition, the group led by Lilja and Vickers included hk2 in a multivariate model to predict the presence of PCa [61][62][63][64][65][66][67]. This model, which incorporates hk2, tPSA, fPSA, and iPSA, together with DRE, the age of the patient, and previous prostate biopsy, improves the accuracy obtained with other models.…”
Section: Four-kallikrein Panelmentioning
confidence: 99%